Vibration Based Energy Harvesting Interface Circuit using Diode-Capacitor Topologies for Low Power Applications - Amirul Adlan Amirnudin; Farahiyah Mustafa; Anis Maisarah Mohd Asry; Sy Yi Sim (Institute of Advanced Engineering and Science, 2017)
A battery-less energy harvesting interface circuit to extract electrical energy from vibration has been proposed in this paper for low power applications. The voltage doubler integrated with DC – DC boost converter circuits were designed and simulated using MultiSIM software. The circuit was then fabricated onto a printed circuit board (PCB), using standard fabrication process. The Cockcroft Walton doubler was chosen to be implemented in this study by utilizing diode-capacitor topologies with additional RC low pass filter. The DC – DC boost converter has been designed using a CMOS step -up DC – DC switching regulators, which are suitable for low input voltage system. The achievement of this interface circuit was able to boost up the maximum voltage of 5 V for input voltage of 800 mV.